2018
DOI: 10.3847/2041-8213/aac2dc
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Milky Way's Halo Age Distribution

Abstract: We present an analysis of the radial age gradients for the stellar halos of five Milky Way (MW) mass-sized systems simulated as part of the Aquarius Project. The halos show a diversity of age trends, reflecting their different assembly histories. Four of the simulated halos possess clear negative age gradients, ranging from approximately −7 to −19 Myr kpc −1 , shallower than those determined by recent observational studies of the Milky Way's stellar halo. However, when restricting the analysis to the accreted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…Depending on the halo, the in-situ fraction contributes about 30 per cent of the inner stellar halo (Tissera et al 2012). A better agreement between observations and simulations is found if the in-situ components are not considered (Carollo et al 2018). This is also the case for other simulations that have been performed with different numerical codes and baryonic physics (e.g.…”
Section: Simulationsmentioning
confidence: 66%
See 1 more Smart Citation
“…Depending on the halo, the in-situ fraction contributes about 30 per cent of the inner stellar halo (Tissera et al 2012). A better agreement between observations and simulations is found if the in-situ components are not considered (Carollo et al 2018). This is also the case for other simulations that have been performed with different numerical codes and baryonic physics (e.g.…”
Section: Simulationsmentioning
confidence: 66%
“…We employ the set of Aquarius haloes analysed by Tissera et al (2012Tissera et al ( , 2013Tissera et al ( , 2014 and Carollo et al (2018) that correspond to MW mass-size galaxies to study the chemical enrichment of baryons during Galactic assembly. These authors found that the stellar halo of the MW is characterised by combination of stellar populations with different chemistry, kinematics, ages, and binding energies depending on their origin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their identification is an important step to understanding galaxy formation. Stars stripped from the merging Galaxy may form structures in the halo in the form of streams, shell or clouds, which can be detected in density space (Ibata et al 2001;Newberg et al 2002;Majewski et al 2003;Belokurov et al 2006), in phase-space (Starkenburg et al 2009;Xue et al 2011;Janesh et al 2016) or in age space (Santucci et al 2015;Carollo et al 2016Carollo et al , 2018.…”
mentioning
confidence: 99%
“…Galaxy formation simulations predict stellar haloes to be formed mainly by the accretion of satellite galaxies, with contributions from in situ stars (Zolotov et al 2009;Font et al 2011;Tissera et al 2012). The properties of these accreted satellites would imprint features in the chemical abundances, age, and kinematics of the stellar populations in the stellar haloes (Tissera et al 2013(Tissera et al , 2014Carollo et al 2018;Fattahi et al 2019;Fernández-Alvar et al 2019). These features could be used to constrain the formation histories of the inner and outer regions of the stellar haloes.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study of age gradients for Milky Way-mass galaxies simulated by the Aquarius Project, Carollo et al (2018) found an overall age gradient in the range of [−8, − 32] Myr kpc −1 , for which the accreted component of the stellar population is largely responsible. These results suggest that the Milky Way formation history is dominated by the accretion of satellite galaxies with dynamical masses less than ∼10 9.5 M e .…”
Section: Introductionmentioning
confidence: 99%